Golgicide A induces pyroptosis of lung cancer stem cells by regulating dTGN formation via GOLPH3/MYO18A complex - Feng Zhang; Sun-Han Zhang; Teng Liu; Guang-Su Xie; Shi-Hua Deng; Ting Zhang; Xiao-Bian Wang; Yue-Yan Yang; Zi-Xin Chen; Dong-Ming Wu; Ying Xu (Stem Cell Research & Therapy)
Abstract Background Lung cancer is a common malignant neoplasm, one of the leading causes of death worldwide. Cancer stem cells (CSCs) drive tumor recurrence, progression, and therapeutic resistance. Thus, targeting CSCs may contribute to lung cancer treatment and improve clinical outcomes. Methods We induced stem cell formation in serum-free suspension culture. Cell viability was assessed using the cell counting-kit 8 assay, and cell membrane integrity was evaluated using the lactate dehydrogenase release assay. Caspase-1 activity assays, western blotting, enzyme-linked immunosorbent assay, and flow cytometry were used to analyze pyroptosis in cells. Confocal microscopy was used to detect protein co-localization. Quantification of fluorescence intensity and co-localization was carried out using ImageJ software. Co-immunoprecipitation was performed to assess the interaction between GOLPH3 and MYO18A. An animal study was conducted to evaluate the effects of golgicide A (GCA) on tumor growth in vivo. Results GCA induced cell death via pyroptosis in both H1650- and A549-derived CSCs. GCA enhanced the binding of GOLPH3 and MYO18A, resulting in trans-Golgi network (TGN) dispersion. In turn, the dispersed TGN (dTGN) recruited NLRP3. Our xenograft animal model study confirmed that GCA can inhibit tumor growth. Conclusions GCA induced pyroptosis by promoting the interaction between GOLPH3 and MYO18A, resulting in dTGN formation in lung CSCs. Our findings provide a novel molecular insight into the anti-cancer activities of GCA in lung CSCs.